Bipolar resistive switching characteristics of tungsten-doped indium–zinc oxide conductive-bridging random access memory. (August 2019) - Gan, Kai-Jhih; Liu, Po-Tsun; Lin, Sheng-Jie; Ruan, Dun-Bao; Chien, Ta-Chun; Chiu, Yu-Chuan; Sze, Simon M.
Abstract: The purpose of this work is to develop a reliable amorphous tungsten-doped indium-zinc oxide based conductive-bridging random access memory (CBRAM). The device with Cu/TiW/InWZnO/Pt structure exhibits stable bipolar resistive switching behavior. The device also shows good non-volatile memory characteristics, such as low operation voltage, on/off resistance ratio (∼10 2 ), high switching endurance (more than 5×10 2 cycles). The temperature coefficient of resistance in the conductive filament confirms that an electro-chemical metallization (ECM) based conduction is observed in the InWZnO device. Furthermore, the temperature retention characteristics and the current transport mechanisms are also investigated. According to our experiments, we propose a model to explain the resistive switching phenomenon observed in our devices. These results have given a great potential for the transparent amorphous oxide semiconductor (TAOS)-based material utilizing in CBRAM stacks and integrating into the display circuits for future memory-in-pixel applications. Highlights: The InWZnO conductive-bridging random access memory (CBRAM) device was fabricated. The on/off resistance ratio (∼10 2 ) and switching endurance (>5×10 2 cycles) are obtained. The current transport mechanisms are also investigated for InWZnO CBRAM. The Cu/TiW/InWZnO/Pt CBRAM device has a great potential for the future memory applications.